Deep-blue emissive and colourless polyimides: optical property tuning by triphenylamino and carbazole chromophores - Šimon, Pavel; Štrojsa, Jakub; Klikar, Milan; Burešová, Zuzana; Růžička, Aleš; Zelenka, Jiří; Kulhánek, Jiří; Tydlitát, Jiří (ROYAL SOC CHEMISTRY, 2024)
Two novel emissive chromophores based on triphenylamine and carbazole have been designed, prepared and further utilized as comonomers towards end-capped emissive colourless polyimides. The polyimide films were fabricated using 1,2,4,5-cyclohexanetetracarboxylicdianhydride/2,2-bis[4-(4-aminophenoxy)phenyl]propane (CHDA-BAPP) and 4,4 '-(hexafluoroisopropylidene)diphthalic anhydride/2,2'-bis(trifluoromethyl)benzidine (6FDA-TFMB), and 5, 1 or 0.1 mol% of comonomer. Fundamental structure-property relationships were elucidated both in solution and the polymeric backbone. Facile planarization/rigidification of the chromophore central donor turned out to be a useful strategy to modulate the optical and thermal properties both of the single molecule and polymeric film. The prepared films are highly thermally stable (T5% up to 526 degrees C) and highly transparent (T400 ranging between 72-86% for 0.1 mol% loadings), and most of the films were colourless. The luminescence colour of the films ranges from yellow-greenish to blue. CHDA-BAPP carbazole-terminated PIs showed deep-blue emission and excellent optical properties with CIEy <= 0.1 and high colour purity (FWHM 38 resp. 42 nm) doped with 1 resp. 0.1 mol% of comonomer. The experimental data were further corroborated by DFT calculations and single crystal X-ray analysis. Two novel emissive chromophores based on triphenylamine and carbazole have been designed, prepared and further utilized as comonomers towards end-capped emissive colourless polyimides.
Modře emisivní a bezbarvé polyimidy: ladění optických vlastností pomocí trifenylaminových a karbazolových chromoforů
Keywords: efficient; fluorescence; derivatives; dynamics; state; fluorescence; chromofory; trifenylamin; karbazol; polyimid